Fabrication of PVDF-HF membrane for bubble-free gas transfer via wet phase inversion - Aksoy, Yunus; Hasar, Halil (Wiley, 2021)
In this study, the characterization of gas permeable hollow fiber membranes fabricated from PVDF polymer by using wet phase inversion method was investigated. During preparation of dope solution for fabrication process, after PVDF polymer was resolved in N-methyl-2-pyrrolidone of 70%-80%, two additives of 5 wt% poly(vinylpyrolidone) K10 and propionic acid (PA) were tried by adding into dope solutions to determine the effect of additives on membrane characterization. SEM images showed that when the PVP K10 additive was used at high PVDF ratio of 25 wt%, a dense structure formed in the inner section and the large finger-like macro-voids reduced through the cross-section of each fiber. FTIR results indicated that both additives were not maintained in the fabricated membranes due to the passage into the water during phase inversion. However, it was realized that using of PVP K10 and PA in the membrane fabrication adversely affected contact angle and gas transfer performance.
Keywords: manufacturing; membranes; structure-property relationships